Are Public Private Partnerships catalysing economic growth in Sub-Saharan Africa? - Matsolo, Nolitha (Graduate School of Business (GSB), 2018)
Governments in Sub-Saharan Africa are experiencing increased pressure to find quick, efficient solutions to the challenge of maintaining, improving and investing in new infrastructure. A range of funding options to finance infrastructure development has been used, however fiscal capacity constraints have become a challenge. To balance availability of funding and economic development constraints, governments in Sub-Saharan Africa have had to find alternative funding methods. Public private partnerships, as an alternative method, have gained prominence in Sub-Saharan Africa. This study therefore explores the notion of the catalytic effect of public private partnerships on economic growth in Sub-Saharan Africa. This study uses unbalanced fixed panel data methodology over a cross section of infrastructure projects across Africa. Data obtained over the period 1994 – 2015 is assessed for the catalytic effects of public private partnerships on economic growth. The results of the empirical analysis indicate that PPPs in SSA over the period tested in the study do have an influence and impact on economic growth. However, the effect of PPPs on economic growth was observed to depend on the proxy used, with significant effect only found when the number of PPPs is employed. The results of the study therefore imply that the PPPs examined here do catalyse economic growth in SSA. Recommendations for future studies include: a further probe into which infrastructure financing method in SSA has the most positive catalytic effect in economic growth. The extent of the impact of unmitigated negative externalities created by the implementation of infrastructure projects financed by PPP arrangements.